PENCIPTAAN MEDIA INFORMASI TABLOID DAN WEBSITE KEPEMUDAAN GEREJA GPdI MARANATHA PURI INDAH - Kurniawan, Daniel; Fianto, Achmad Yanu Alif; Sutikno, Sutikno (Jurnal Art Nouveau, 2015)
Abstract: Â GPdI maranatha is a church that develops. Maranatha own organization to bless the who are around him.The great commission has become the job of every church to run. In netted with the great commission of media is one of the to carry it out. Tabloid is media information suitable in conveying and embrace the young. The purpose of making media this information, that youth the church GPdI who was in the castle beautiful could be more known by peoples beyond sidoarjo. And can inform youth the church GPdI that may be free to know activities maranatha puri indah. Making media this information based on the data and survey the directly in the church GPdI maranatha puri indah. The result of making information media is expected to inform to the whole church and introduced the church gpdi maranatha to the community.Â Keywords: Maranatha, the Great Commission, Media information.